Orthogonal Decomposition in Omega-Weighted Classes of Functions Subharmonic in the Half-Plane - A. M. Jerbashian; D. Vergas (ՀՀ ԳԱԱ հրատ.)
The paper gives a harmonic, ω -weighted, half-plane analog of W. Wirtinger’s projection theorem and its (1 r )α − weighted extension by M. Djrbashian, also an orthogonal decomposition is obtained for some ω -weighted classes of functions subharmonic in half plane. Տրված է Վ. Վիրտինգերի պրոեկցիոն թեորեմի ու դրա համար Մ. Մ. Ջրբաշյանի գտած (1 r )α − կշռային ընդլայնման հարմոնիկ համանմանը կիսահարթության մեջ, ինչպես նաև օրթոգոնալ վերլուծություն կիսահարթությունում սուբհարմոնիկ որոշ ω - կշռային դասերում։ Дан гармонический, ω -весовой, полуплоскостной аналог проекционной теоремы В. Виртингера и ее (1 r )α − весового расширения, найденного М. М. Джрбашяном. Установлено также ортогональное разложение в некоторых ω -весовых классах функций, субгармонических в полуплоскости.
Keywords: Mathematics; Science